1994
DOI: 10.1021/bi00188a016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nucleotides and Actin on the Intramolecular Crosslinking of Myosin Subfragment-1

Abstract: The heavy chain of myosin subfragment-1 (S1) is cleaved by limited trypsinolysis into three fragments, 27, 50, and 20 kDa--aligned in this order from the N-terminus. The tertiary structure of the molecule is essentially not affected by trypsinolysis. The spatial relations between the various regions of the molecule and the nucleotide- and actin-induced intramolecular movements were studied by cross-linking tryptic S1 with N-(ethoxycarbonyl)-2-ethoxy-1,2-dihydroquinoline (EEDQ), 1-(3-dimethylaminopropyl)-3-ethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The proteolysis of the cross-linked S1(A1) resulted in the formation of the 31-, 46-, and 47-kDa fluorescent products, whereas cleavage of the cross-linked S1(A2) generated fluorescent products of 40 kDa and 47 kDa. The 47-kDa products, obtained during digestion of both isoforms correspond to earlier identified products of the cross-linking between N-and C-terminal tryptic fragments of the heavy chain of S1, whereas the 46-kDa product in S1(A1) and the 40-kDa product in S1(A2) are formed by the cross-linking of the C-terminal heavy chain fragment to the respective light chains (20,21). Molecular mass of the 46-kDa product indicates that it contains the A1 light chain FIG.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The proteolysis of the cross-linked S1(A1) resulted in the formation of the 31-, 46-, and 47-kDa fluorescent products, whereas cleavage of the cross-linked S1(A2) generated fluorescent products of 40 kDa and 47 kDa. The 47-kDa products, obtained during digestion of both isoforms correspond to earlier identified products of the cross-linking between N-and C-terminal tryptic fragments of the heavy chain of S1, whereas the 46-kDa product in S1(A1) and the 40-kDa product in S1(A2) are formed by the cross-linking of the C-terminal heavy chain fragment to the respective light chains (20,21). Molecular mass of the 46-kDa product indicates that it contains the A1 light chain FIG.…”
Section: Resultssupporting
confidence: 65%
“…Earlier studies have only demonstrated that both A2 light chain and A1 light chain devoid the N-terminal part can be cross-linked with EDC to the N-and C-terminal fragments of the heavy chain (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Preferentially intramolecular cross-linking of protein occurred which could increase the conformation stability. For this reason, these conditions were also used to introduce additional tertiary structure into proteins (Blotnick and Muhlrad 1994). Consequently, by changing reaction conditions, intermolecular cross-linking (resulting in a decreased protein solubility) or intramolecular cross-linking (mainly leading to conformation stabilization) can be achieved, thereby controlling the specific properties of the final product.…”
Section: Influence Of Reaction Time and Ph Levelmentioning
confidence: 99%